Dysregulated Macrophages Are Present in Bleomycin‐Induced Murine Laryngotracheal Stenosis. (17th June 2015) - Hillel, Alexander T.; Samad, Idris; Ma, Garret; Ding, Dacheng; Sadtler, Kaitlyn; Powell, Jonathan D.; Lane, Andrew P.; Horton, Maureen R.
Abstract : Objective: To define the inflammatory cell infiltrate preceding fibrosis in a laryngotracheal stenosis (LTS) murine model. Study Design: Prospective controlled murine study. Setting: Laboratory. Subjects and Methods: Chemomechanical injury mice (n = 44) sustained bleomycin‐coated wire‐brush injury to the laryngotracheal complex while mechanical injury controls (n = 42) underwent phosphate‐buffered saline (PBS)–coated wire‐brush injury. Mock surgery controls (n = 34) underwent anterior transcervical tracheal exposure only. Inflammatory and fibrosis protein and gene expression were assessed in each condition. Immunohistochemistry served as a secondary outcome. Results: In chemomechanical injury mice, there was an upregulation of collagen I ( P <. 0001, P <. 0001), Tgf‐β ( P =. 0023, P =. 0008), and elastin ( P <. 0001, P <. 0001) on day 7; acute inflammatory gene Il1β ( P =. 0027, P =. 0008) on day 1; and macrophage gene CD11b ( P =. 0026, P =. 0033) on day 1 vs mechanical and mock controls, respectively. M1 marker inducible nitric oxide synthase (iNOS) expression decreased ( P =. 0014) while M2 marker Arg1 ( P =. 0002) increased on day 7 compared with mechanical controls. Flow cytometry demonstrated increased macrophages ( P =. 0058, day 4) and M1 macrophages ( P =. 0148, day 4; P =. 0343, day 7; P =. 0229, day 10) compared to mock controls. There were similarities between chemomechanical and mechanical injury mice with an increase in M2 macrophages at day 10 ( P =. 0196). Conclusions: The bleomycin‐induced LTS mouse model demonstrated increased macrophages involved with the development of fibrosis. Macrophage immunophenotype suggested that dysregulated M2 macrophages have a role in abnormal laryngotracheal wound healing. These data delineate inflammatory cells and signaling pathways in LTS that may potentially be modulated to lessen fibroblast proliferation and collagen deposition.